A recipe for thriving in nursing homes: A meta‐ethnography. (19th February 2021) - Baxter, Rebecca; Corneliusson, Laura; Björk, Sabine; Kloos, Noortje; Edvardsson, David
Abstract: Aim: To explore contributors for thriving in nursing homes by evaluating, analysing and synthesizing peer‐reviewed qualitative literature on the topic. Background: Thriving is a positive life‐world concept that has been explored by several qualitative studies; however, descriptions of thriving and contributors to thriving have not been compared or contrasted among different studies and contexts, nor have they been reviewed and synthesized. Design: Qualitative meta‐ethnography. Data sources: Four electronic databases were searched in October 2019, with sources published between 2000 and 2019 included. Review methods: Sources of peer‐reviewed literature that employed qualitative methods to explore thriving in nursing homes were evaluated. In total, 1, 017 sources were screened at title‐level, 95 advanced to abstract‐level review and 11 were assessed at full‐text level. Each source was evaluated by two researchers independently in relation to methodological quality and relevance to the study aim. Themes pertaining to thriving in nursing homes were extracted, interpreted and synthesized. Results: In total, seven sources of peer‐reviewed literature were included. Two main themes illustrating the contributors to thriving were identified: ingredients for thriving (subthemes: personal contributors and social contributors) and environment for thriving (subthemes: spacial contributors and societal contributors). Conclusion: Contributors to thriving in nursing homes include personal attributes, relationships with others, the lived environment and societal structures. Thriving for older people could thereby be defined as a holistic concept denoting lived experiences of situated contentment. Future studies should explore different temporal facets of thriving in the nursing home setting. Impact: This meta‐synthesis proposes a 'recipe' for thriving as comprising the right ingredients and the right environment, determined by the preferred 'taste' of the individual person. The proposed definition and contributors illuminate thriving as a positive life‐world concept that is based on one's lived experiences and context.